FACTORS THAT INFLUENCE THE APPLICATION OF UNIT WORKING BUDGET OF MEDAN CITY GOVERNMENT WITH MONITORING AND EVALUATION AS A MODERATING VARIABLE - Dwiyana, Nova (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of this study was to analyze the influence of the budget planning, quality of human resources, bureaucratic reform, work discipline and motivation with monitoring and evaluation as moderating variable on the budget absorption of Medan City Government. The study used causal research method. The population was 57 SKPDs (Regional Work Unit) that consisted of PPK-SKPD (Financial Management Official of SKPD) and treasurers of Medan City Government, and all of them were used as the samples (census sampling). Primary data were gathered by using questionnaires. Hypothesis was tested by using multiple regression analysis and moderating test with residual test. The result of the study showed that the budget planning, quality of human resources, bureaucratic reform, work discipline and motivation had significant influence on the budget absorption simultaneously. Partially, the budget planning, quality of human resources, bureaucratic reform, work discipline and motivation had significant influence on the budget absorption. Monitoring and evaluation as moderating variable could not moderate the correlation of the budget planning, quality of human resources, bureaucratic reform, work discipline and motivation with the budget absorption of Medan City Government.